Singlet superconductivity enhanced by charge order in nested twisted bilayer graphene Fermi surfaces. (October 2018) - Laksono, Evan; Leaw, Jia Ning; Reaves, Alexander; Singh, Manraaj; Wang, Xinyun; Adam, Shaffique; Gu, Xingyu
Abstract: Using the continuum model for low energy non-interacting electronic structure of moiré van der Waals heterostructures developed by Bistritzer and MacDonald [1], we study the competition between spin, charge, and superconducting order in twisted bilayer graphene. Surprisingly, we find that for a range of small angles inclusive of the so-called magic angle, this model features robust Fermi pockets that preclude any Mott insulating phase at weak coupling. However, a Fermi surface reconstruction at θ  ≳ 1.2° gives emergent van Hove singularities without any Fermi pockets. Using a hot-spot model for Fermi surface patches around these emergent saddle points, we develop a random-phase approximation from which we obtain a phase diagram very similar to that obtained recently by Isobe, Yuan, and Fu using the parquet renormalization group [2] but with additional insights. For example, our model shows strong nesting around time-reversal symmetric points at a moderate doping of ∼2 × 10 11  cm −2 away from the van Hove singularity. When this nesting dominates, we predict that charge-order enhances singlet superconductivity, while spin-order suppresses superconductivity. Our theory also provides additional possibilities for the case of unnested Fermi surfaces. Highlights: Our work shows that the magic angles are plagued by Fermi pockets which within weak coupling preclude Mott insulating phase. When the Fermi surface around time reversal saddle points is nested, we find the insulating phase is charge ordered and the superconductivity is a spin singlet. Our model makes additional predictions that spin order enhances d-wave superconductivity or charge order enhances s-wave superconductivity when the Fermi surface is not nested.